Direct Electrodeposition of Bimetallic Nanostructures on Co-Based MOFs for Electrochemical Sensing of Hydrogen Peroxide - Xie, Yixuan; Shi, Xianhua; Chen, Linxi; Lu, Jing; Lu, Xiange; Sun, Duanping; Zhang, Luyong (Frontiers in Chemistry, 2022)
Hydrogen peroxide (H2O2) is the most significant reactive oxygen species in biological systems. Here, we reported an electrochemical sensor for the detection of hydrogen peroxide (H2O2) based on bimetallic gold-platinum nanoparticles (Au3Pt7 NPs) supported by Co-based metal organic frameworks (Co-MOFs). First, Au3Pt7 NPs, with optimal electrocatalytic activity and accessible active surface, can be deposited on the surface of the Co-MOF-modified glassy carbon electrodes (Au3Pt7/Co-MOFs/GCE) by one-step electrodeposition method. Then, the electrochemical results demonstrated that the two-dimensional (2D) Co-MOF nanosheets as the supporting material displayed better electrocatalytic properties than the 3D Co-MOF crystals for reduction of H2O2. The fabricated Au3Pt7/2D Co-MOF exhibited high electrocatalytic activity, and the catalytic current was linear with H2O2 concentration from 0.1 μM - 5 mM, and 5 mM - 60 mM with a low detection limit (LOD) of 0.02 μM (S/N = 3). The remarkable electroanalytical performance of Au3Pt7/2D Co-MOF can be attributed to the synergistic effect of the high dispersion of the Au3Pt7 NPs with the marvelous electrochemical properties and the 2D Co-MOF with high-specific surface areas. Furthermore, this sensor has been utilized to detect H2O2 concentrations released from the human Hela cells. This work provides a new method for improving the performance of electrochemical sensors by choosing the proper support materials from diverse crystal morphology materials.